Ageing, multimorbidity, and quality of life: a mediation analysis using longitudinal ageing study in India - Singh, Bharti; Kumar, Ajay (Frontiers in Public Health, 2025)
BackgroundThe ageing population in India is growing rapidly, but the decline in healthy life expectancy is more pronounced. This trend has been compounded and constituted by poor quality of life (QoL), with the salient underlying role of multimorbidity as the leading risk factor. This study primarily aimed to assess the intermediating role of multimorbidity as the risk factor for exogenous socioeconomic and demographic factors on QoL.MethodsThis study used data from 73,396 individuals aged 45 years and above from the Longitudinal Ageing Study in India (LASI), Wave – 1, 2017–18. Multimorbidity was defined as the simultaneous existence of two or more chronic conditions in an individual. The QoL score was constructed using Principal Component Analysis (PCA) by utilizing 21 factors under six domains (physical health, psychological health, social relationship, environmental satisfaction, life satisfaction and general health), with the composite QoL score ranging from 0 to 100. Further, the Structural equation model (SEM) was used to assess the role of multimorbidity as the intermediating risk factor for exogenous factors on QoL.ResultsDistributions of morbidities burden were skewed toward non-communicable diseases (NCDs) and sequentially escalated multimorbidity burden was observed among the oldest of old age groups. After the age of 75, there was a steep decline in the gradient of QoL score. The SEM results showed a substantial rise in multimorbidity burden leading to poor QoL with a magnitude of β = −2.39, p < 0.001. Age and sex of the respondents exhibited a significant negative impact on QoL, impacting it directly (β = −1.25; β = −1.19) as well as indirectly through multimorbidity (β = −0.11). In contrast, childhood health demonstrated a solely direct impact on QoL, with no significant indirect pathway through multimorbidity. This study further revealed that urban residence had a pronounced positive direct effect on QoL (β = 0.9, p < 0.001).ConclusionThis study underscores the role of multimorbidity as a key mediator between socioeconomic and demographic factors on QoL among older adults in India. With the increasing prevalence of multimorbidity, policies should prioritize integrated geriatric healthcare services. Strengthening healthcare for early screening and affordable chronic disease management is essential.